T cell epitope immunotherapy induces a CD4+ T cell population with regulatory activity. - Adrienne Verhoef; Clare Alexander; A Barry Kay; Mark Larché (PLoS Medicine, 2005)
BACKGROUND: Synthetic peptides, representing CD4(+) T cell epitopes, derived from the primary sequence of allergen molecules have been used to down-regulate allergic inflammation in sensitised individuals. Treatment of allergic diseases with peptides may offer substantial advantages over treatment with native allergen molecules because of the reduced potential for cross-linking IgE bound to the surface of mast cells and basophils. METHODS AND FINDINGS: In this study we address the mechanism of action of peptide immunotherapy (PIT) in cat-allergic, asthmatic patients. Cell-division-tracking dyes, cell-mixing experiments, surface phenotyping, and cytokine measurements were used to investigate immunomodulation in peripheral blood mononuclear cells (PBMCs) after therapy. Proliferative responses of PBMCs to allergen extract were significantly reduced after PIT. This was associated with modified cytokine profiles generally characterised by an increase in interleukin-10 and a decrease in interleukin-5 production. CD4(+) cells isolated after PIT were able to actively suppress allergen-specific proliferative responses of pretreatment CD4(neg) PBMCs in co-culture experiments. PIT was associated with a significant increase in surface expression of CD5 on both CD4(+) and CD8(+) PBMCs. CONCLUSION: This study provides evidence for the induction of a population of CD4(+) T cells with suppressor/regulatory activity following PIT. Furthermore, up-regulation of cell surface levels of CD5 may contribute to reduced reactivity to allergen.